Fine-Granular Model Merge Solution For Model-Based Version Control System - Mehmood, Waqar; Shah, Nadir; Khan, Majid Jamal; Memon, Mukhriar; Ikramullah, M (Malaysian Journal of Computer Science, 2016)
Software Configuration Management (SCM) aims to provide a controlling mechanism for the evolution of software artifacts created during software development process. Controlling software artifacts evolution requires many activities to be carried out such as, construction and creation of versions, computation of mappings and differences between versions, merging (i.e. combining of two or more versions) and so on. Traditional SCM systems are file-based SCM systems, which are not adequate for performing software configuration management activities. File-based SCM systems consider software artifacts as a set of text files, while today’s software development is model-driven and models are the main artifacts produced in the early phases of software development process. New challenges of model mappings, differencing, merging, and conflict detection arise when applying file-based solution to model-driven software. The goal of this paper is to develop a configuration management solution for model merging and conflict resolution that overcomes the challenges faced by traditional SCM systems for model-based development. We represent models at finegrained level as graph structures, which is an intermediate representation based on graph theory. Our approach follows a 3-way model merge process, where a base and its derived versions are used for comparison. To differentiate between conflicted and non-conflicted cases, we have defined different merge cases, and established a merge policy based on merge cases. Merge cases are used along with the comparison result in order to perform conflict resolution and merge operation. We performed a controlled experiment using open source eclipse modeling framework and compare our approach with an open source tool Eclipse Modeling Framework (EMF) Compare. The results proved the accuracy and efficiency of our proposed approach.